Analysis of the Influence of Digital Marketing, Product Quality, and Price on Samsung Product Purchase Decisions on the Shopee Marketplace - Sri Nawangsari; Trifena Gracia (Asosiasi Dosen Muda Indonesia, 2026)
This study aims to analyze the influence of digital marketing, product quality, and price on Samsung product purchase decisions on the Shopee marketplace. The research employed a quantitative approach using primary data collected through questionnaires. The population consisted of consumers who had purchased Samsung products through Shopee. A non-probability sampling method with a purposive sampling technique was applied, resulting in 150 valid respondents. The data were analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination. The results show that digital marketing has a positive and significant effect on purchase decisions. Product quality also has a positive and significant effect on purchase decisions and is identified as the most dominant variable. In addition, price has a positive and significant effect on purchase decisions. The Adjusted R Square value of 0.419 indicates that digital marketing, product quality, and price explain 41.9% of the variation in Samsung product purchase decisions, while the remaining 58.1% is influenced by other factors outside this study. These findings imply that Samsung should strengthen its digital marketing strategy, maintain product quality, and offer competitive prices to increase consumer purchase decisions on Shopee.